Effect of phase transformation on corrosion behaviour of Zn–22Al alloys. (February 2014) - Zhang, Y. M.; Yang, L. J.; Zeng, X. D.; Wang, Y. L.; Song, Z. L.
<x content-type="archive" xml:space="preserve">Abstract</x> The effect of phase transformation on the corrosion behaviour of Zn–22Al (wt-%) alloys immersed in NaCl solution (3·5 wt-%) at room temperature was investigated. As cast Zn–22Al alloys were isothermally heated at 300 and 250°C (the eutectoid point is 277°C) respectively and then cooled by various rates. Isothermally heated below the eutectoid point, the corrosion resistance of the alloys increased with the decreasing cooling rate. However, when the isothermal heating temperature was above the eutectoid point, the corrosion resistance of Zn–22Al alloys increased with the increasing cooling rate. It can be attributed to the existence of α2 phase, which may lead to smaller potential difference between the microgalvanic cells.